Quartzite procurement in conglomerates and deposits: Geoarchaeological characterization of potential catchment areas in the central part of the Cantabrian Region, Spain. Issue 3 (5th January 2021) - Prieto, Alejandro; Yusta, Iñaki; García‐Rojas, Maite; Arrizabalaga, Alvaro; Baena Preysler, Javier
Abstract: Raw material characterization in Paleolithic archaeology has widened our knowledge of Middle Paleolithic societies. Procurement of raw material, specifically flint, has allowed the tracing of the mobility of both stones and people, as well as selective processes to obtain specific types or even extraction activities. The analysis of quartzite has also developed in recent years, providing an opportunity to better understand prehistoric societies. This study characterizes the procurement strategies implemented by Middle Paleolithic people in the mountainous region of the Picos de Europa. To this end, we present a comprehensive characterization of potential catchment areas: massive outcrops, conglomerates, and river deposits. The exploitation of quartzite at the sites of El Habario and El Arteu allows us to understand the territorial management of this mountainous area through the combination of selective processes and mobility mechanisms in lower and middle altitudes. These perspectives enable us to view the mountainous region not as a barrier but as an environmental mosaic managed by Middle Paleolithic groups. This study shows strategies that bring together direct and embedded procurement based on both intensive and extensive searches. These discourses are more closely related to the daily life of people than those only considering the mobility of people and objects. Abstract : A comprehensive geoarchaeological research project based on the integration of a geographic information system, field survey, stereomicroscopy, and thin‐section petrography, is presented to characterize potential procurement areas of quartzite. The application of this methodology in the Deva, Cares, and Güeña valleys and in three different geological contexts; massive outcrops, conglomerates, and secondary deposits, suggest potential acquisition processes of lithic resources. The analysis of the quartzite assemblages of El Habario and El Arteu unveils complex management of terrain based on a mobility mechanism that connects middle altitude plateaus with open and lower river valleys, as well as intensive and extensive procurement mechanisms of raw material.